Structural and functional characterization of barium zirconium titanate/epoxy composites - González Garcia, Filiberto; Foschini, César Renato [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Moura, Francisco; Simões, Alexandre Zirpoli [UNESP] (My University, 2011)
The dielectric behavior of composite materials (barium zirconium titanate / epoxy system) was analyzed as a function of ceramic concentration. Structure and morphologic behavior of the composites was investigated by X-ray Diffraction (XRD), Fourier transformed infrared spectroscopy (FT-IR), Raman spectroscopy, field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) analyses. Composites were prepared by mixing the components and pouring them into suitable moulds. It was demonstrated that the amount of inorganic phase affects the morphology of the presented composites. XRD revealed the presence of a single phase while Raman scattering confirmed structural transitions as a function of ceramic concentration. Changes in the ceramic concentration affected Raman modes and the distribution of particles along into epoxy matrix. Dielectric permittivity and dielectric losses were influenced by filler concentration.
Keywords: Composite materials; Oxides; Polymers; Electron diffraction